PERAN PEKERJA SOSIAL DALAM MENANGANI KASUS PERDAGANGAN MANUSIA PADA WANITA DAN ANAK-ANAK - Aisyah Rasya Syafa Azzahra; Ifally Pramesia Putri Peachilia; Eva Nuriyah Hidayat (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Criminal cases of human trafficking in women and children become an international spotlight. This cases that begin with a job seekers who migrate outside the region. Many factors cause this trade, including the lack of public knowledge about human trafficking information, poor families who come from remote or slum areas, limited education, family economic crisis, immigrant workers, school dropouts, victims family violence, women and street children, and sexual exploitation. Although this crime is still difficult and complicated to overcome. However, the social workers can help provide a protection and services to victims. There are several institutions that deal with this problem, including the Women's Social Protection House, the Ministry of Women's Empowerment and Child Protection, and the Ministry of Law and Human Rights, Social Affairs, the National Agency for the Placement and Protection of Indonesian Migrant Workers (BNP2TKI), the Ministry of Social Affairs, the Indonesian Police and Attorney General's Office. This study aims to determine the role of social workers related to problems in handling cases of trafficking in women and children. The research method technique uses a literature review technique that contains theories that are relevant to the research problems. A social workers in practice have several roles that must be carried out, a role as a facilitator, a role as a broker, a role as a mediator, a role as a defender and a role as a protector, where are used in several interventions for handling the rehabilitation of human trafficking in women and children.